Analisis Pengaruh Lingkungan Kerja Non-Fisik, Insentif, dan Pelatihan terhadap Kinerja Karyawan pada Hotel Royal Jember - Apvellyo Dhymas Adjie Pangestu; Tatit Diansari Reskiputri; Rusdiyanto Rusdiyanto (Universitas Nusantara PGRI Kediri, 2025)
The quality of a hotel is determined by various factors, including prompt and friendly service, cleanliness, complete facilities, and a comfortable atmosphere. The staff's ability to effectively address guest needs is crucial. Hotels that consistently maintain quality tend to build customer loyalty. This research was conducted with the aim of analyzing the influence of non-physical working conditions, incentives, and training programs on employee performance at the Royal Jember Hotel. The method used in this study is an associative quantitative approach, involving 50 respondents selected through a non-probability sampling technique using the saturation method. Data collection was carried out by distributing questionnaires to participants. The stages of data analysis include testing the validity and reliability of the instrument, evaluating classical assumptions, multiple linear regression analysis, hypothesis testing, and calculating the coefficient of determination to measure the contribution of independent variables to the dependent variable. The research findings indicate that the variables of the non-physical working environment, incentives, and training have a positive and significant influence on employee performance at the Royal Jember Hotel. This is reflected in the coefficient of determination (R²) value which reached 79.1%, indicating the contribution of these three variables in explaining the variability of employee performance.